2019
DOI: 10.7150/ijms.28595
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study of a Parkinson's Disease Model of Undifferentiated SH-SY5Y Cells Induced by a Proteasome Inhibitor

Abstract: Parkinson's disease (PD) is one of the most common nervous system degenerative diseases. However, the etiology of this disease remains elusive. Here, a proteasome inhibitor (PSI)-induced undifferentiated SH-SY5Y PD model was established to analyze protein alterations through proteomic study. Methods: Cultured undifferentiated SH-SY5Y cells were divided into a control group and a group treated with 2.5 µM PSI (PSI-treated group). An methyl thiazolyl tetrazolium (MTT) assay was applied to detect cell viability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…These cells express multiple 14-3-3 isoforms, including 14-3-3 ε and ζ that were of particular interest in our study. It was recently shown that these 14-3-3 isoforms are subject to ubiquitin regulated proteasomal degradation in SHSY5Y cells (Jiang et al 2019). Our observation that ebselen treatment triggered ubiquitin-mediated proteasomal degradation of 14-3-3s in SHSY5Y cells (Fig.…”
Section: < Fig 6 > Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These cells express multiple 14-3-3 isoforms, including 14-3-3 ε and ζ that were of particular interest in our study. It was recently shown that these 14-3-3 isoforms are subject to ubiquitin regulated proteasomal degradation in SHSY5Y cells (Jiang et al 2019). Our observation that ebselen treatment triggered ubiquitin-mediated proteasomal degradation of 14-3-3s in SHSY5Y cells (Fig.…”
Section: < Fig 6 > Discussionsupporting
confidence: 63%
“…It nevertheless possible, that the effect of ebselen on 14-3-3 levels may be indirect, by i.e. increasing the phosphorylation, ubiquitination, or other covalent modification of 14-3-3s, as such modifications are reported to trigger 14-3-3 degradation (Jiang et al 2019;Chen et al 2015).…”
Section: < Fig 6 > Discussionmentioning
confidence: 99%
“…Finally, 3-phosphoserine was converted into L-serine by PSP [23]. L-serine is an important precursor involved in various processes, such as synthesis of proteins and phospholipids as well as the synthesis of tetrahydrofolate metabolites and specific amino acids, namely glycine, cysteine, D-serine [24][25]. Previous studies have shown that L-serine supplementation can attenuate alcoholic fatty liver formation in mice and rats [26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 3-phosphoserine is converted to Lserine by PSP [24]. L-serine is an important precursor involved in various processes, such as synthesis of proteins and phospholipids as well as the synthesis of tetrahydrofolate metabolites and speci c amino acids, namely glycine, cysteine and D-serine [25,26]. Previous studies have shown that L-serine supplementation can attenuate alcoholic fatty liver formation in mice and rats [27].…”
Section: Discussionmentioning
confidence: 99%